Corrosion-resistant refractory material for lithium carbonate acidizing calcining kiln and preparation method of corrosion-resistant refractory material

By using modified silicon micropowder refractories prepared in lithium carbonate acidification roasting kilns, the problem of poor corrosion resistance of existing refractories is solved, and higher high temperature and corrosion resistance are achieved, which extends the Service life.

CN119409487AActive Publication Date: 2025-02-11YIXING LONGCHANG REFRACTORIES CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411557226.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing lithium carbonate acidified roasting kiln refractories have poor corrosion resistance, which leads to acid gas seeping into the refractory, causing corrosion, reducing thermal insulation performance and service life.

Method used

Using the combination of bauxite, silicon carbide powder, corundum powder, modified silicon micropowder, calcium aluminate cement and specific admixtures and water reducing agents, the preparation method and preparation process of modified silicon micropowder are formed with high volume density and Refractory with good corrosion resistance.

Benefits of technology

It significantly improves the high temperature and corrosion resistance of the refractory, extends the service life, and prevents acid gas from entering the refractory.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of refractory material preparation, in particular to a corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln and a preparation method. The refractory material comprises the following components in parts by weight: 50-60 parts of bauxite, 8-10 parts of silicon carbide powder, 10-20 parts of corundum powder, 15-25 parts of modified silica powder, 6-8 parts of calcium aluminate cement, 8-12 parts of an additive and 1-3 parts of a water reducing agent. According to the refractory material, the bauxite serves as a main material, the high temperature resistance and strength of the refractory material are improved through the corundum powder and the silicon carbide powder, pores in the refractory material are filled with the modified silica powder, and the admixture can form a silicon dioxide cross-linked structure among the modified silica powder, so that the volume density of the refractory material is improved, and the pores in the refractory material are reduced; acid gas is prevented from entering the refractory material, so that the refractory material has good high temperature resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory preparation, and in particular to a corrosion-resistant refractory used in a lithium carbonate acidification roasting kiln and a preparation method thereof. Background Art

[0002] With the application of lithium-ion batteries in electronic products, new energy electric vehicles and other fields, the demand for lithium carbonate, as an important basic raw material for lithium-ion batteries, has increased dramatically. The current lithium carbonate production process mainly involves transformation roasting, acid roasting, leaching, purification, concentration, lithium precipitation, cleaning, drying, crushing and packaging of lithium concentrate.

[0003] Acid roasting is to mix lithium ore powder with excess concentrated sulfuric acid and then put it into a lithium carbonate acid roasting kiln for roasting. Since the existing acid roasting kiln refractory has poor corrosion resistance, the acid gas generated during acid roasting will penetrate into the interior of the refractory, causing corrosion to the interior of the refractory, resulting in poor thermal insulation performance of the refractory and shortened service life. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln and a preparation method thereof.

[0005] The technical solution of the present invention is: a corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln, which comprises the following components by weight: 50-60 parts of bauxite, 8-10 parts of silicon carbide powder, 10-20 parts of corundum powder, 15-25 parts of modified silicon micropowder, 6-8 parts of calcium aluminate cement, 8-12 parts of admixture, and 1-3 parts of water reducing agent.

[0006] Description: The above-mentioned refractory uses bauxite as the main material, and uses corundum powder and silicon carbide powder to improve the high temperature resistance and strength of the refractory. The modified silicon micropowder is used to fill the internal pores of the castable, and the admixture can form a silicon dioxide cross-linked structure between the modified silicon micropowder, thereby increasing the bulk density of the refractory, reducing the pores in the refractory, and preventing acidic gases from entering the interior of the refractory, so that the refractory has good high temperature resistance and corrosion resistance.

[0007] Furthermore, the preparation method of the modified silicon powder comprises the following steps:

[0008] S1. Put the silicon micropowder into a tartaric acid solution with a mass concentration of 10-15%, stir for 1-2 hours and then filter to obtain the pretreated silicon micropowder; wherein the mass ratio of the silicon micropowder to the tartaric acid solution is 1:10-15;

[0009] S2, adding benzoquinone into anhydrous ethanol, stirring until completely dissolved, to obtain a benzoquinone solution; wherein the mass ratio of benzoquinone to anhydrous ethanol is 1:80-110;

[0010] S3. Add the pretreated silicon micropowder into the benzoquinone solution, and use a dilute hydrochloric acid solution to adjust the pH value of the benzoquinone solution to 5-6, then stir the benzoquinone solution at 40-60°C for 2-4 hours, filter and dry to obtain modified silicon micropowder; wherein the mass ratio of the pretreated silicon micropowder to the benzoquinone solution is 1:25-30.

[0011] Description: The modified silica micropowder is prepared by pretreating the silica micropowder so that the carboxyl groups on the tartaric acid are combined with the silanol groups on the surface of the silica micropowder, and the surface of the silica micropowder is loaded with hydroxyl groups, so as to improve the dispersibility and wetting properties of the silica micropowder. The hydroxyl groups on the surface of the silica micropowder can form covalent bonds with benzoquinone, and the benzoquinone is loaded onto the silica micropowder, so that the modified silica micropowder can effectively inhibit the polymerization of silanol intermediates during the mixing process of the refractory material, thereby avoiding the rapid solidification of the refractory material.

[0012] Furthermore, in step S3, the drying temperature is 110-120° C. and the drying time is 30-40 min.

[0013] Note: limiting the drying temperature can ensure that the silicon micropowder is fully dried and avoid agglomeration of the silicon micropowder, which will result in the silicon micropowder being unable to be evenly dispersed in the refractory.

[0014] Furthermore, in step S1, the particle size of the silicon powder is 0.1-0.3 μm.

[0015] Note: Limiting the particle size of silicon micropowder can ensure that the silicon micropowder can fully fill the pores of the refractory material and ensure the volume density of the refractory material.

[0016] Furthermore, the water reducing agent is any one of polyacrylate, polystyrene ester or polyacrylamide, or a mixture of multiple thereof in any ratio.

[0017] Description: Water reducing agent can improve the bonding properties of refractory materials, reduce porosity, and reduce the amount of water used in the preparation process.

[0018] Furthermore, the additive is a mixture of 3-aminopropyltriethoxysilane and tetraethoxysilane in a mass ratio of 1:1 to 1.8.

[0019] Note: The tetraethoxysilane in the above-mentioned additives can be hydrolyzed and polycondensed under the action of 3-aminopropyltriethoxysilane to form a cross-linked structure of silicon dioxide between the modified silicon micropowders, thereby increasing the bulk density of the refractory.

[0020] On the other hand, the method for preparing the corrosion-resistant refractory material for the lithium carbonate acidification roasting kiln comprises the following steps:

[0021] Step 1, adding bauxite, silicon carbide powder, corundum powder, modified silicon micropowder, calcium aluminate cement, and water reducing agent into a stirring tank according to the weight parts, stirring for 10 to 20 minutes to obtain dry material;

[0022] Step 2: Fill the mixing tank with nitrogen to pressurize it. The filling parameters are as follows:

[0023] 1) 0.03~0.05m 3 Inflate at a speed of / min, stir the dry materials during the inflation process, and add additives into the mixing tank until the pressure in the mixing tank reaches 0.3-0.5MPa, and maintain the pressure for 15-20min;

[0024] 2) 0.01~0.02m 3 / min, and during the deflation process, the stirring tank is heated to raise the temperature of the stirring tank from room temperature to 120-140°C, and then a sodium hydroxide solution with a mass concentration of 0.2-0.4% is added into the stirring tank until the pressure in the stirring tank reaches 0.1-0.2MPa, and the temperature and pressure are maintained for 1-3h; wherein, the amount of sodium hydroxide solution added accounts for 5-8% of the mass of the dry material;

[0025] 3) 0.02~0.04m 3 Inflate at a rate of / min, and cool the mixing tank by circulating cooling water until the pressure in the mixing tank reaches 0.3-0.4MPa, and maintain the pressure for 30-40min;

[0026] Step 3: Depressurize the mixing tank, and obtain refractory material after depressurization.

[0027] Description: The above preparation method first pressurizes the stirring tank with nitrogen to increase the density of the refractory material, and allows the additive to fully penetrate into the interior of the refractory material under pressure, and then reduces the pressure and raises the temperature of the stirring tank, so that tetraethoxysilane can be hydrolyzed under the action of sodium hydroxide solution to generate silanol intermediates, and 3-aminopropyltriethoxysilane can form a covalent bond with the carboxyl group on the surface of the modified silicon micropowder, and then pressurizes and cools and cooperates with benzoquinone loaded on the surface of the modified silicon micropowder to inhibit the polymerization of the silanol intermediates and avoid rapid solidification of the refractory material. When the refractory material is used for the first time, benzoquinone will decompose at high temperature, causing the silanol intermediates to continue to polymerize, and form a silicon dioxide cross-linked structure under the cross-linking action of 3-aminopropyltriethoxysilane, filling the pores between the silicon micropowders, and improving the volume density and corrosion resistance of the refractory material.

[0028] Furthermore, the heating rate during the heating process is 12-14°C / min.

[0029] Note: Limiting the heating rate can ensure the full hydrolysis of tetraethoxysilane and avoid the expansion of nitrogen in the stirring tank due to excessive temperature increase.

[0030] Furthermore, the cooling rate is 5-8°C / min until the temperature in the stirring tank drops to 15-25°C.

[0031] Note: By cooling, the polymerization of silanol intermediates can be inhibited and the rapid solidification of refractory materials can be avoided.

[0032] The beneficial effects of the present invention are:

[0033] (1) The refractory of the present invention uses bauxite as the main material, and uses corundum powder and silicon carbide powder to improve the high temperature resistance and strength of the refractory. The modified silicon micropowder is used to fill the internal pores of the castable, and the additive can form a silicon dioxide cross-linked structure between the modified silicon micropowder, thereby increasing the bulk density of the refractory, reducing the pores in the refractory, and preventing acidic gases from entering the interior of the refractory, so that the refractory has good high temperature resistance and corrosion resistance.

[0034] (2) The tetraethoxysilane in the admixture of the present invention can be hydrolyzed under the action of sodium hydroxide solution to generate silanol intermediates, and the benzoquinone loaded on the surface of the modified silicon micropowder can inhibit the polymerization of the silanol intermediates, thereby avoiding the rapid solidification of the refractory. During the use of the refractory, the benzoquinone will decompose at high temperature, causing the silanol intermediates to continue to polymerize and form a silicon dioxide cross-linked structure under the cross-linking action of 3-aminopropyltriethoxysilane, thereby filling the pores between the silicon micropowders and improving the bulk density and corrosion resistance of the refractory. DETAILED DESCRIPTION

[0035] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0036] Embodiment 1: A corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln comprises the following components by weight: 55 parts of bauxite, 9 parts of silicon carbide powder, 15 parts of corundum powder, 20 parts of modified silicon micropowder, 7 parts of calcium aluminate cement, 10 parts of admixture, and 2 parts of water reducer; wherein the water reducer is polyacrylate, the particle size of silicon carbide powder is 10 to 20 μm, the particle size of corundum powder is 1 to 5 μm, and the admixture is 3-aminopropyltriethoxysilane and tetraethoxysilane mixed in a mass ratio of 1:1.5;

[0037] The preparation method of the modified silicon micropowder comprises the following steps:

[0038] S1. Put the silicon micropowder into a tartaric acid solution with a mass concentration of 12%, stir for 1.5 hours and then filter to obtain the pretreated silicon micropowder; wherein the mass ratio of the silicon micropowder to the tartaric acid solution is 1:12, and the particle size of the silicon micropowder is 0.1-0.3 μm;

[0039] S2, adding benzoquinone into anhydrous ethanol, stirring until completely dissolved, to obtain a benzoquinone solution; wherein the mass ratio of benzoquinone to anhydrous ethanol is 1:100;

[0040] S3, adding the pretreated silicon micropowder into the benzoquinone solution, and adjusting the pH value of the benzoquinone solution to 5.5 with a dilute hydrochloric acid solution, then stirring the benzoquinone solution at 50°C for 3 hours, filtering and drying to obtain modified silicon micropowder; wherein the mass ratio of the pretreated silicon micropowder to the benzoquinone solution is 1:28, the drying temperature is 115°C, and the drying time is 35 minutes;

[0041] The preparation method of the above refractory material comprises the following steps:

[0042] Step 1, adding bauxite, silicon carbide powder, corundum powder, modified silicon powder, calcium aluminate cement, and water reducing agent according to the weight parts into a stirring tank, stirring for 15 minutes to obtain a dry material;

[0043] Step 2: Fill the mixing tank with nitrogen to pressurize it. The filling parameters are as follows:

[0044] 1) 0.04m 3 Inflate at a speed of / min. Stir the dry materials during the inflation process and add additives into the mixing tank until the pressure in the mixing tank reaches 0.4MPa, and maintain the pressure for 18min.

[0045] 2) 0.015m 3 / min, and the stirring tank is heated during the deflation process to raise the temperature of the stirring tank from room temperature to 130°C, and then a sodium hydroxide solution with a mass concentration of 0.3% is added into the stirring tank until the pressure in the stirring tank reaches 0.15MPa, and the temperature and pressure are kept for 2h; wherein, the amount of sodium hydroxide solution added accounts for 6% of the mass of the dry material, and during the heating process, the temperature rise rate in the stirring tank is 13°C / min;

[0046] 3) 0.03m 3 / min, and cool the stirring tank by circulating cooling water until the pressure in the stirring tank reaches 0.35MPa, and maintain the pressure for 35min; wherein, the cooling rate is 6℃ / min, until the temperature in the stirring tank drops to 20℃;

[0047] Step 3: Depressurize the mixing tank, and obtain refractory material after depressurization.

[0048] Example 2: This example is basically the same as Example 1, except that it includes the following ingredients by weight: 50 parts of bauxite, 8 parts of silicon carbide powder, 10 parts of corundum powder, 15 parts of modified silica powder, 6 parts of calcium aluminate cement, 8 parts of admixture, and 1 part of water reducer.

[0049] Example 3: This example is basically the same as Example 1, except that it includes the following ingredients by weight: 60 parts of bauxite, 10 parts of silicon carbide powder, 20 parts of corundum powder, 25 parts of modified silica powder, 8 parts of calcium aluminate cement, 12 parts of admixture, and 3 parts of water reducer.

[0050] Example 4: This example is basically the same as Example 1, except that the additive is a mixture of 3-aminopropyltriethoxysilane and tetraethoxysilane in a mass ratio of 1:1.

[0051] Example 5: This example is basically the same as Example 1, except that the admixture is a mixture of 3-aminopropyltriethoxysilane and tetraethoxysilane in a mass ratio of 1:1.8.

[0052] Example 6: This example is basically the same as Example 1, except that the pretreated silicon powder is added to the benzoquinone solution, and the pH value of the benzoquinone solution is adjusted to 5 using a dilute hydrochloric acid solution.

[0053] Example 7: This example is basically the same as Example 1, except that the pretreated silicon powder is added to the benzoquinone solution, and the pH value of the benzoquinone solution is adjusted to 6 using a dilute hydrochloric acid solution.

[0054] Example 8: This example is basically the same as Example 1, except that the mass ratio of the pretreated silicon micropowder to the benzoquinone solution is 1:25.

[0055] Example 9: This example is basically the same as Example 1, except that the mass ratio of the pretreated silicon micropowder to the benzoquinone solution is 1:30.

[0056] Embodiment 10: This embodiment is basically the same as Embodiment 1, except that:

[0057] 1) 0.03m 3 Inflate at a rate of / min until the pressure in the mixing tank reaches 0.3MPa;

[0058] 2) 0.01m 3 / min until the pressure in the mixing tank reaches 0.1MPa;

[0059] 3) 0.02m 3 / min until the pressure in the mixing tank reaches 0.3MPa.

[0060] Embodiment 11: This embodiment is basically the same as Embodiment 1, except that:

[0061] 1) 0.05m 3 Inflate at a rate of / min until the pressure in the mixing tank reaches 0.5MPa;

[0062] 2) 0.02m 3 / min until the pressure in the mixing tank reaches 0.2MPa;

[0063] 3) 0.04m 3 / min until the pressure in the mixing tank reaches 0.4MPa.

[0064] Example 12: This example is basically the same as Example 1, except that the stirring tank is heated during the degassing process so that the temperature of the stirring tank is increased from room temperature to 120°C.

[0065] Example 13: This example is basically the same as Example 1, except that the stirring tank is heated during the degassing process so that the temperature of the stirring tank is increased from room temperature to 140°C.

[0066] Example 14: This example is basically the same as Example 1, except that the cooling rate is 5°C / min until the temperature in the stirring tank drops to 15°C.

[0067] Example 15: This example is basically the same as Example 1, except that the cooling rate is 8°C / min until the temperature in the stirring tank drops to 25°C.

[0068] Comparative Example 1: Taking Example 1 as a reference, the modified silicon micropowder was replaced with ordinary silicon micropowder.

[0069] Comparative Example 2: Using Example 1 as a reference, no admixture was used.

[0070] Comparative Example 3: Taking Example 1 as a reference, ordinary silicon powder was used and benzoquinone was directly added to the dry material.

[0071] Comparative Example 4: Taking Example 1 as a reference, the pressure in the stirring tank was kept constant at 0.4 MPa.

[0072] Comparative Example 5: Using Example 1 as a reference, the temperature in the stirring tank was kept at room temperature without changing.

[0073] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the refractory, the refractory prepared in each embodiment is placed in a mold, and after vibration, it is baked at 160°C for 28 hours to obtain a sample. The sample of each embodiment is immersed in a 40% sulfuric acid solution for 30 days, and the mass loss rate and compressive strength reduction rate before and after immersion are calculated. The specific exploration is as follows:

[0074] Experimental Example 1: Investigating the influence of refractory composition on refractory performance

[0075] Using Examples 1 to 5 and Comparative Examples 1 to 3 as experimental comparisons, the refractory properties under different compositions are shown in Table 1 below:

[0076] Table 1 Refractory properties under different compositions

[0077] Group Quality loss rate Compressive strength reduction rate Example 1 0.22% 2.2% Example 2 0.29% 3.3% Example 3 0.27% 3.0% Example 4 0.25% 2.6% Example 5 0.30% 3.5% Comparative Example 1 0.89% 6.1% Comparative Example 2 0.98% 6.4% Comparative Example 3 0.71% 5.5%

[0078] It can be seen from the data in Table 1 that compared with Examples 1, 2, and 3, the mass loss rate and compressive strength decrease rate of the refractory of Example 1 are the lowest, indicating that the refractory of Example 1 has better acid corrosion resistance, so the refractory composition of Example 1 is better;

[0079] Compared with Examples 1, 4, and 5, the mass loss rate and compressive strength decrease rate of the refractory of Example 1 are the lowest, indicating that the refractory of Example 1 has better acid corrosion resistance. This may be because under the additive ratio of Example 1, the hydrolysis of tetraethoxysilane is most sufficient, so the additive ratio selected in Example 1 is optimal;

[0080] Compared with Comparative Example 1, after using unmodified ordinary silicon powder, the mass loss rate and compressive strength decrease rate of the refractory material increased. This may be because the ordinary silicon powder cannot inhibit the polycondensation after the hydrolysis of tetraethoxysilane, and the refractory material has not solidified at this time, and the formed silicon dioxide cannot effectively fill the gaps between the silicon powders. Therefore, the refractory material composition selected in Example 1 is better;

[0081] Compared with Comparative Example 2, in Example 1, after no admixture was used, the mass loss rate and compressive strength decrease rate of the refractory material increased. This may be because the silica cross-linked structure cannot be formed inside the refractory material, and there are more pores in the refractory material structure, so that the acid can easily enter the refractory material. Therefore, the refractory material composition selected in Example 1 is better;

[0082] Compared with Comparative Example 3, Example 1 uses ordinary silicon micropowder and directly adds benzoquinone to the dry material. The mass loss rate of the refractory and the decrease rate of the compressive strength are increased. This may be because benzoquinone cannot be evenly distributed on the silicon micropowder, resulting in benzoquinone being unable to effectively inhibit the polycondensation of tetraethoxysilane after hydrolysis. Therefore, the refractory component selected in Example 1 is better;

[0083] Experimental Example 2: Investigating the influence of modified silicon powder preparation parameters on refractory properties

[0084] Using Example 1 and Examples 6 to 9 as experimental comparisons, the refractory properties of modified silicon micropowder under different preparation parameters are shown in Table 2 below:

[0085] Table 2 Refractory properties of modified silicon powder under different preparation parameters

[0086] Group Quality loss rate Compressive strength reduction rate Example 1 0.22% 2.2% Example 6 0.26% 2.9% Example 7 0.27% 3.2% Example 8 0.24% 2.5% Example 9 0.26% 2.7%

[0087] It can be seen from the data in Table 2 that compared with Examples 1, 6, and 7, the mass loss rate and compressive strength decrease rate of the refractory of Example 1 are the lowest, indicating that the refractory of Example 1 has better acid corrosion resistance. This may be because at the pH value of the benzoquinone solution of Example 1, the benzoquinone loading amount on the surface of the silicon powder is greater, so the pH value of the benzoquinone solution selected in Example 1 is optimal;

[0088] Compared with Examples 1, 8, and 9, the refractory mass loss rate and compressive strength decrease rate of Example 1 are the lowest. This may be because at the ratio of pretreated silicon micropowder to benzoquinone solution, the benzoquinone loaded on the surface of the modified silicon micropowder can better condense the silanol intermediate and can be fully decomposed at high temperature. Therefore, the ratio of pretreated silicon micropowder to benzoquinone solution selected in Example 1 is optimal.

[0089] Experimental Example 3: Investigating the influence of inflation parameters on refractory performance

[0090] Using Example 1, Examples 10-11 and Comparative Example 4 as experimental comparisons, the refractory properties under different inflation parameters are shown in Table 3 below:

[0091] Table 3 Refractory properties under different inflation parameters

[0092] Group Quality loss rate Compressive strength reduction rate Example 1 0.22% 2.2% Example 10 0.29% 3.4% Embodiment 11 0.28% 3.0% Comparative Example 4 0.48% 4.6%

[0093] It can be seen from the data in Table 3 that compared with Examples 1, 10 and 11, the mass loss rate and compressive strength decrease rate of the refractory of Example 1 are the lowest, indicating that the refractory of Example 1 has better acid corrosion resistance. This may be because under the inflation parameters selected in Example 1, the internal pores of the refractory are the least, so the inflation parameters selected in Example 1 are optimal;

[0094] Compared with comparative example 4, in Example 1, the mass loss rate of the refractory material and the decrease rate of the compressive strength increased after constant pressure was adopted. This may be because tetraethoxysilane cannot be fully hydrolyzed when constant pressure is adopted. Therefore, the inflation parameters selected in Example 1 are better.

[0095] Example 4: Investigating the effect of mixing tank temperature on refractory properties

[0096] Using Example 1, Examples 12 to 15 and Comparative Example 5 as experimental comparisons, the refractory properties of the stirring tank at different temperatures are shown in Table 4 below:

[0097] Table 4 Refractory properties of the mixing tank at different temperatures

[0098] Group Quality loss rate Compressive strength reduction rate Example 1 0.22% 2.2% Example 12 0.31% 3.5% Embodiment 13 0.29% 3.3% Embodiment 14 0.26% 2.8% Embodiment 15 0.28% 2.9% Comparative Example 5 0.42% 4.5%

[0099] It can be seen from the data in Table 4 that compared with Examples 1, 12, and 13, the mass loss rate and compressive strength decrease rate of the refractory material of Example 1 are the lowest, indicating that the refractory material of Example 1 has better acid corrosion resistance. This may be because tetraethoxysilane can be fully hydrolyzed under the temperature parameters selected in Example 1, so the temperature parameters selected in Example 1 are better;

[0100] Compared with Examples 1, 14, and 15, the mass loss rate and compressive strength decrease rate of the refractory material of Example 1 are the lowest, indicating that the refractory material of Example 1 has better acid corrosion resistance. This may be because the cooling parameters of Example 1 have a better inhibitory effect on the polymerization reaction of the silanol intermediate, so the cooling parameters selected in Example 1 are better;

[0101] Compared with Comparative Example 5, after the temperature of the stirring tank was kept at room temperature, the mass loss rate of the refractory material and the decrease rate of the compressive strength increased in Example 1. This may be because tetraethoxysilane cannot be fully hydrolyzed. Therefore, the temperature parameters selected in Example 1 are better.

Claims

1. A corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln, characterized in that: The composition includes the following components by weight: 50-60 parts of bauxite, 8-10 parts of silicon carbide powder, 10-20 parts of corundum powder, 15-25 parts of modified silicon micropowder, 6-8 parts of calcium aluminate cement, 8-12 parts of admixture, and 1-3 parts of water reducing agent.

2. The corrosion-resistant refractory material for lithium carbonate acidification roasting kiln according to claim 1, characterized in that: The preparation method of the modified silicon micropowder comprises the following steps: S1. Put the silicon micropowder into a tartaric acid solution with a mass concentration of 10-15%, stir for 1-2 hours and then filter to obtain the pretreated silicon micropowder; wherein the mass ratio of the silicon micropowder to the tartaric acid solution is 1:10-15; S2, adding benzoquinone into anhydrous ethanol, stirring until completely dissolved, to obtain a benzoquinone solution; wherein the mass ratio of benzoquinone to anhydrous ethanol is 1:80-110; S3. Add the pretreated silicon micropowder into the benzoquinone solution, and use a dilute hydrochloric acid solution to adjust the pH value of the benzoquinone solution to 5-6, then stir the benzoquinone solution at 40-60°C for 2-4 hours, filter and dry to obtain modified silicon micropowder; wherein the mass ratio of the pretreated silicon micropowder to the benzoquinone solution is 1:25-30.

3. A corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln according to claim 2, characterized in that: In step S3, the drying temperature is 110-120° C. and the drying time is 30-40 minutes.

4. The corrosion-resistant refractory material for lithium carbonate acidification roasting kiln according to claim 2, characterized in that: In step S1, the particle size of the silicon powder is 0.1-0.3 μm.

5. The corrosion-resistant refractory material for lithium carbonate acidification roasting kiln according to claim 1, characterized in that: The water reducing agent is any one of polyacrylate, polystyrene ester or polyacrylamide, or a mixture of multiple types in any ratio.

6. The corrosion-resistant refractory material for lithium carbonate acidification roasting kiln according to claim 1, characterized in that: The additive is prepared by mixing 3-aminopropyltriethoxysilane and tetraethoxysilane in a mass ratio of 1:1 to 1.

8.

7. A method for preparing a corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln, for preparing the corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, adding bauxite, silicon carbide powder, corundum powder, modified silicon micropowder, calcium aluminate cement, and water reducing agent into a stirring tank according to the weight parts, stirring for 10 to 20 minutes to obtain dry material; Step 2: Fill the mixing tank with nitrogen to pressurize it. The filling parameters are as follows: 1) 0.03~0.05m 3 Inflate at a speed of / min, stir the dry materials during the inflation process, and add additives into the mixing tank until the pressure in the mixing tank reaches 0.3-0.5MPa, and maintain the pressure for 15-20min; 2) 0.01~0.02m 3 / min, heating the stirring tank during the deflation process to raise the temperature of the stirring tank from room temperature to 120-140°C, then adding a sodium hydroxide solution with a mass concentration of 0.2-0.4% into the stirring tank until the pressure in the stirring tank reaches 0.1-0.2MPa, and maintaining the temperature and pressure for 1-3h; wherein the amount of sodium hydroxide solution added accounts for 5-8% of the mass of the dry material; 3) 0.02~0.04m 3 Inflate at a rate of / min, and cool the mixing tank by circulating cooling water until the pressure in the mixing tank reaches 0.3-0.4MPa, and maintain the pressure for 30-40min; Step 3: Depressurize the mixing tank, and obtain refractory material after depressurization.

8. The method for preparing a corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln according to claim 7, characterized in that: The heating rate of the heating process is 12-14°C / min.

9. The method for preparing a corrosion-resistant refractory material for a lithium carbonate acidification roasting kiln according to claim 7, characterized in that: The cooling rate is 5-8°C / min until the temperature in the stirring tank drops to 15-25°C.

Citation Information

Patent Citations

  • Preparation method of delayed coagulation type ether polycarboxylate water reducing agent

    CN110642993A

  • Ester ring epoxy acrylate hybrid silicon resin, preparation method and application

    CN113831536A

  • Glass mold prepared from kaolin and preparation method thereof

    CN118405928A

  • Special refractory castable for industrial silicon refining ladle and preparation method of special refractory castable

    CN118545989A

  • Nonfibrous castable refractory concrete having high deflection temperature and high compressive strength and process

    US4174972A